POTRAIT OF ENGLISH TEACHING IN ELEMENTARY SCHOOL OF SD PATRA MANDIRI 2 PALEMBANG VIEWED FROM KURIKULUM MERDEKA - Sulthan Ghazi Al Ghifari; Djunaidi; Marleni (Universitas PGRI Palembang, 2025)
This research investigates the implementation of the Kurikulum Merdeka in the context of English language instruction at SD Patra Mandiri 2 Palembang, with particular attention to its learner-centered orientation and the pedagogical challenges encountered by educators. Employing a qualitative descriptive approach, data were gathered through classroom observations, an in-depth interview with an English teacher, and questionnaires administered to 22 fifth-grade students. The findings indicate that the curriculum is enacted through dynamic and participatory strategies such as educational games, collaborative group discussions, and project-based learning exemplified by activities like the